Relasi Mursyid – Salik: Komunikasi Edukatif AL-Ghazali Dalam Ihya ‘Ulum Al-din - Aas Asrulsani; Gigin Sugiwa; Agus Wahyudin; Elpata Sahrizal Firdaus; Ziyad Fakhrur Razi (Institut Agama Islam Persis Bandung, 2026)
This study examines the pedagogical relationship between mursyid (spiritual guide) and salik (spiritual learner) through the perspective of educational communication based on Imam al-Ghazali’s teachings in Ihya’ Ulum al-Din. The urgency of the study lies in the fact that many previous works emphasize hierarchical and normative aspects of the mursyid–salik relationship, while the communicative mechanisms that shape spiritual character remain insufficiently explored. Therefore, this research focuses on identifying how spiritual education is communicated and internalized through exemplary guidance. This study employs a qualitative textual method (library research) by analyzing sections of Ihya’ concerning the ethics of the teacher–student relationship, soul purification, and moral cultivation. Social Learning Theory is used to interpret al-Ghazali’s concepts of uswah (modeling), suhbah (companionship), talqin (transmitting creed), muhasabah (corrective dialogue), and riyadah (discipline) as communicative processes that reinforce spiritual values. The findings reveal that guidance in al-Ghazali’s perspective is not merely a transfer of knowledge, but primarily a transfer of adab, by which the learner acquires spiritual maturity through persistent modeling, emotional closeness, and persuasive communication. This study concludes that the mursyid acts as a transformative educator whose role remains relevant for strengthening ethical-spiritual communication in contemporary Islamic education.